At the statue of Venus a musical scene for soprano and chamber orchestra - Heggie, Jake 1961-; McNally, Terrence 1938-2020 (Bent Pen Music, Inc., 2016)
Tells the story of a woman waiting in an art museum for a man she has not yet met